K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 2 2017

9x(2016-x)  =2016

2016-x       =2016:9

2016-x       =224

        x       =2016-224

        x       =1792

Vậy x=1792

8 tháng 2 2017

9 x ( 2016 - x ) = 2016

        2016 - x = 2016 : 9

         2016 - x = 224

                   x = 2016 - 224

                   x = 1792

Vậy x = 1792

9 tháng 12 2019

Thay \(2016=xyz\)vào biểu thức ta được

\(A=\frac{x^2yz}{xy+x^2yz+xyz}+\frac{y}{yz+y+xyz}+\frac{z}{xz+z+1}\)

   \(=\frac{x^2yz}{xy\left(1+xz+z\right)}+\frac{y}{y\left(z+1+xz\right)}+\frac{z}{xz+z+1}\)

   \(=\frac{xz}{xz+z+1}+\frac{1}{xz+z+1}+\frac{z}{xz+z+1}=\frac{xz+z+1}{xz+z+1}=1\)

Vậy \(A=1\)

12 tháng 11 2020

Vì \(xyz=2016\)

\(\Rightarrow A=\frac{2016x}{xy+2016x+2016}+\frac{y}{yz+y+2016}+\frac{z}{xz+z+1}\)

\(=\frac{xyz.x}{xy+xyz.x+xyz}+\frac{y}{yz+y+xyz}+\frac{z}{xz+z+1}\)

\(=\frac{x^2yz}{xy+x^2yz+xyz}+\frac{y}{y\left(z+1+xz\right)}+\frac{z}{xz+z+1}\)

\(=\frac{x^2yz}{xy\left(1+xz+z\right)}+\frac{1}{xz+z+1}+\frac{z}{xz+z+1}\)

\(=\frac{xz}{xz+z+1}+\frac{1}{xz+z+1}+\frac{z}{xz+z+1}\)

\(=\frac{xz+1+z}{xz+z+1}=1\)

26 tháng 11 2016

X.(X^2014+2016)>0

do đó x>0

do X^2+2016>0 

nên X-3<0

Suy ra:x<3

18 tháng 9 2015

x=2015

=> x+1=2016

=> A=x2016-(x+1).x2015+(x+1).x2014-(x+1).x2013+...+(x+1)x2-(x+1)x+2016

=x2016-x2016-x2015+x2015+x2014-x2014-x2013+...+x3+x2-x2-x+2016

=-x+2016

=-2015+2016

=1

Vậy A=1.

20 tháng 10 2019

\(x^4+2016x^2+2017x+2016\)

\(=x^4+2016x^2+2016x+x+2016\)

\(=\left(x^4+x\right)+\left(2016x^2+2016x+2016\right)\)

\(=x\left(x^3+1\right)+2016\left(x^2+x+1\right)\)

\(=x\left(x+1\right)\left(x^2+x+1\right)+2016\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^2+x+2016\right)\)